2012
DOI: 10.1177/1074248412458723
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cardioprotection With Ischemic Preconditioning in Aging Hearts: Role of Sirtuin 1?

Abstract: The effectiveness of ischemic preconditioning (IPC) to protect the heart against ischemia/reperfusion injury (IRI) declines with age. The deacetylase protein sirtuin 1 (Sirt 1) confers myriad functions including longevity and cardioprotection against IRI. As such, Sirt 1 may be a potential candidate to explain the protective effect of IPC. We aim to explore the role of Sirt 1 in the loss of the cardioprotective effect of IPC with age. Isolated hearts from young (9 weeks) and older (12-18 months) Long-Evans rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Although experimental IPC models have been shown to evoke potent anti-ischemic defence47, IPC-induced protection is diminished in old animals, affording no protection in ischemic heart, brain and liver254849505152. Renal protection by IPC in aged animals has not been tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental IPC models have been shown to evoke potent anti-ischemic defence47, IPC-induced protection is diminished in old animals, affording no protection in ischemic heart, brain and liver254849505152. Renal protection by IPC in aged animals has not been tested yet.…”
Section: Discussionmentioning
confidence: 99%
“…The SIRT1 inhibitor splitomycin inhibited cardioprotection (Nadtochiy et al , 2011b). The cardiac protection associated with ischemic preconditioning decreases with age, and while SIRT1 also decreases with age, one study suggested these factors are independent (Adam et al , 2013). The cardiac protection in long term caloric restriction also is associated with an increase in nuclear but not total SIRT1 (Shinmura et al , 2008).…”
Section: Pharmacologic Therapiesmentioning
confidence: 99%
“…Therefore, although intracellular Nampt is essential to the cardiac myocyte survival, exogenous Nampt could be detrimental demanding fine balance between its synthesis and secretion. Interestingly, the cardiac protection conferred by IPC deteriorates with age [244]. The lack of ischemic tolerance in aged hearts is mainly accounted for by a reduced SIRT1 expression and activity although one study has ruled out the role of SIRT1 [244].…”
Section: Role Of Sirtuins In Tissue Injury and Repairmentioning
confidence: 99%
“…Interestingly, the cardiac protection conferred by IPC deteriorates with age [244]. The lack of ischemic tolerance in aged hearts is mainly accounted for by a reduced SIRT1 expression and activity although one study has ruled out the role of SIRT1 [244]. …”
Section: Role Of Sirtuins In Tissue Injury and Repairmentioning
confidence: 99%